KAJIAN KONSEPTUAL MODEL PEMBELAJARAN BLENDED LEARNING BERBASIS WEB UNTUK MENINGKATKAN HASIL BELAJAR DAN MOTIVASI BELAJAR - Ahmad Kholiqul Amin (Jurnal Pendidikan Edutama, 2017)
Abstract: Conceptual Analysis of  Web basis Blended learning teaching model to improve the student’s achievement and motivation.. In this article, describe the content of some research result journals which is focuses on the blended learning teaching model. The research result which is analyzed based on searching result of online journal database such as database Education Resources Information Center (ERIC), The turkish Online Journal of Education Tecnology (TOJET) dan Academics’ research center (ARC). In this article, for about twenty international journals focused on blended learning teaching model. This article discuss based on blended learning limitation. i.e.  the concept of blended learning, research method, technique of collecting data, research  instrument, data analysis. The discussion of this article partly as a reference to conduct further research. The result of this conceptual study from some journals show that blended learning is a mix method among conventional learning and online learning. The students expected to be actively to find out the learning technique  which is comfortable for the students. Teacher has a function as mediator, facilitator, and also as a friend who always build conducive situation for the students. Blended learning will also strength conventional model through the development of technology for education. Beside, the result of the journals can be concluded that the average of the research result in blended learning also contribute to the student’s achievement .Keywords: Abstrak: Kjian Konseptual Model Pemebelajaran Blended Learning berbasis web untuk meningkatkan hasil belajar dan motivasi belajar. Pada artikel ini memaparkan kajian isi jurnal dari beberapa hasil penelitian yang difokuskan pada model pembelajaran blended learning. Hasil jurnal penelitian yang dianalisis berdasarkan dari hasil penelusuran database jurnal online seperti database Education Resources Information Center (ERIC), The turkish Online Journal of Education Tecnology (TOJET) dan Academics’ research center (ARC) dll. Pada artikel ini jurnal yang dikaji berjumlah kurang lebih 20 jurnal internasional yang berfokus pada model pembelajaran blended learning. Artikel ini membahas berdasarkan ruang lingkup dari blended learning, konsep dari blended learning, metode penelitian, teknik pengumpulan data,  instrument penelitian, analisis data. Pengkajian pada artikel ini sebagai rujukan untuk melakukan penelitian selanjutnya. Hasil dari kajian konsep dari beberapa jurnal bahwa model blended learning adalah pencampuran model pembelajaran konvensional dengan belajar secara online. Peserta didik diharapkan selalu aktif dan dapat menemukan cara belajar yang sesuai bagi dirinya. Guru hanya berfungsi  sebagai  mediator, fasilitor dan  teman  yang  membuat  situasi  yang  kondusif untuk  terjadinya konstruksi pengetahuan  pada  diri peserta didik.  Blended  learning ini  akan memperkuat  model  belajar  konvensional melalui pengembangan teknologi pendidikan. Selain itu hasil kajian pada jurnal dapat disimpulkan bahwa rata-rata hasil penelitian blended learning juga memberikan pengaruh terhadap hasil belajar.Kata Kunci : Blended Learning, Hasil Belajar